2021
DOI: 10.1101/mcs.a005801
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-emergent neuroendocrine prostate cancer with a germline BRCA2 mutation: identification of a candidate reversion mutation associated with platinum/PARP-inhibitor resistance

Abstract: Neuroendocrine prostate cancer (NEPC) is a highly aggressive histologic subtype of prostate cancer associated with a poor prognosis. Its incidence is expected to increase as castration-resistant disease emerges from the widespread use of potent androgen receptor-targeting therapies, such as abiraterone and enzalutamide. Defects in homologous recombination repair genes, such as BRCA1/2 , are also being increasingly detected in individuals with advanced prostate cancer. We present the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Recent studies have shown, indeed, that pancreatic NENs can be associated with germline pathogenic variants in genes involved in DNA damage repair, such as MutY DNA Glycosylase, Checkpoint Kinase 2, and above all BRCA (22,38,39). Two case reports described patients with prostate NEC, a highly aggressive histologic subtype of prostate cancer, one with germline and the second with somatic BRCA mutation, confirming platinum and Poly[ADP-ribose] polymerase 1 (PARP) inhibitor sensibility similar to that of malignancies that frequently present this type of alteration (40,41). Interestingly, in one of these cases, a novel reversion mutation that restores Brca 1/2 function was described, which might be the reason for primary resistance to PAPR inhibitors (41).…”
Section: Genomic Alterationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies have shown, indeed, that pancreatic NENs can be associated with germline pathogenic variants in genes involved in DNA damage repair, such as MutY DNA Glycosylase, Checkpoint Kinase 2, and above all BRCA (22,38,39). Two case reports described patients with prostate NEC, a highly aggressive histologic subtype of prostate cancer, one with germline and the second with somatic BRCA mutation, confirming platinum and Poly[ADP-ribose] polymerase 1 (PARP) inhibitor sensibility similar to that of malignancies that frequently present this type of alteration (40,41). Interestingly, in one of these cases, a novel reversion mutation that restores Brca 1/2 function was described, which might be the reason for primary resistance to PAPR inhibitors (41).…”
Section: Genomic Alterationsmentioning
confidence: 84%
“…Two case reports described patients with prostate NEC, a highly aggressive histologic subtype of prostate cancer, one with germline and the second with somatic BRCA mutation, confirming platinum and Poly[ADP-ribose] polymerase 1 (PARP) inhibitor sensibility similar to that of malignancies that frequently present this type of alteration (40,41). Interestingly, in one of these cases, a novel reversion mutation that restores Brca 1/2 function was described, which might be the reason for primary resistance to PAPR inhibitors (41). In addition, the role of Schlafen (SLFN) 11 was also recently explored in SCLC.…”
Section: Genomic Alterationsmentioning
confidence: 88%
“…Recently PARP-inhibitors have been approved for therapy in PCa patients with DDR pathway mutations and have already been used to treat t-NEPC patients with such aberrations, though only with limited success [ 129 ]. PARP1 is a chromatin associated enzyme modifying various nuclear proteins by poly-ADP-ribosylation, but it also functions as transcriptional coactivator for E2F1 [ 130 ].…”
Section: Mechanisms Of T-nepc Developmentmentioning
confidence: 99%
“…Pandya et al found that olaparib administered as a maintenance therapy to a patient with NEPC carrying germline BRCA2 mutations led to survival for 18 months post-NEPC diagnosis. 18 Herein, we report another patient with SCCP who benefitted considerably from olaparib.…”
Section: Discussionmentioning
confidence: 91%